2009
DOI: 10.1111/j.1472-765x.2008.02493.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of fengycins on the production of fumonisin B1fromFusarium verticillioides

Abstract: Aim:  To understand the role of fengycins in regulating the fumonisin B1 (FB1) production of Fusarium verticillioides. Methods and Results:  The mass ratio of FB1 to mycelia was determined in order to identify the effect of fengycins on FB1 production. It was shown that the amount of FB1 produced by unit mass mycelia decreased to 28% of the control. Results from mycelia resuspension with fengycins also demonstrated that fengycins had a potent impact on FB1 production. Gene expression patterns using quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…MTA144 (Meca et al, 2013), could encode aminotransferase FBI, showing strong fumonisin degrading activity . Hu et al reported that fengycin could inhibit the transcription of some key genes involved in the production of FB1 (Hu et al, 2009). Combined with the result in this study, we can conclude that the increase of fengycin expression could be the main cause of its enhancement of FB1-degrading ability.…”
Section: Discussionsupporting
confidence: 69%
“…MTA144 (Meca et al, 2013), could encode aminotransferase FBI, showing strong fumonisin degrading activity . Hu et al reported that fengycin could inhibit the transcription of some key genes involved in the production of FB1 (Hu et al, 2009). Combined with the result in this study, we can conclude that the increase of fengycin expression could be the main cause of its enhancement of FB1-degrading ability.…”
Section: Discussionsupporting
confidence: 69%
“…Moreover, we further exemplify some specificity regarding the target species. As occasionally reported, iturins and fengycins may interfere with some intracellular processes in fungal plant pathogens notably leading to inhibition of toxin formation (Hu et al ., ). However, the most evidenced effect of these LPs is the disruption of membrane integrity, leading to the lysis of various fungal life stages like mycelium, conidia or zoospores for oomycete pathogens (Raaijmakers et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Similarly, the antifungal activities of B. subtilis strains and other biological agents against A. flavus and AFB1-production have been reported in several studies ( Dorner et al, 1998 ; Dorner, 2004 ; Mohammadipour et al, 2009 ; Reddy et al, 2009 ; Zhang et al, 2007 ). However, contrary to our results, several studies indicated that although Bacillus spp., exhibit considerable antifungal activities against some phytopathogenic fungi but their inhibitory activities against A. flavus are no significant ( Hu et al, 2009 ; Sun et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrates that antifungal activity of B. subtilis UTBSP1, producer of both fengycin and surfactin, is attributed to both antibiotics. However, some Bacillus strains which produce surfactin and/or fengycin couldn’t inhibit the growth of A. flavus ( Hu et al, 2009 ; Sun et al, 2006 ), whereas ( Mohammadipour et al, 2009 ) reported that B. subtilis BS119m, as a surfactin-producer in a high level, completely inhibit the growth of A. flavus . Furthermore, this study indicates that surfactin and fengycin act in a synergistic manner and provide stronger antifungal activity against A. flavus R5, similar to the synergistic antifungal manners of surfactin and iturin ( Maget-Dana and Ptak, 1990 ), surfactin and fengycin ( Ongena et al, 2007 ; Sun et al, 2006 ) and iturin and fengycin ( Romero et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%